Visit to Solar Park I A Hands-On Learning Experience for Solar Cell Technology Students - Saifful Kamaluddin, Muzakir (Faculty of Industrial Sciences and Technology, UMPSA, 2024)
On 8 May 2024, a group of six undergraduate students from the BAppSc Material Technology with Honours program, currently enrolled in the BSP3503 (Solar Cell Technology) course for Semester II 23/24, paid an educational visit to Solar Park I. Accompanying them were two postgraduate students, led by Assoc. Prof. Dr. Saifful Kamaluddin Muzakir.